The design of high performance mechatronics : high-tech functionality by multidisciplinary system integration - Schmidt, Robert Munnig (Delft University Press, 2014)
Since they entered our world around the middle of the 20th century, the application of mechatronics has enhanced our lives with functionality based on the integration of electronics, control systems and electric drives. This book deals with the special class of mechatronics that has enabled the exceptional levels of accuracy and speed of high-tech equipment applied in the semiconductor industry, realising the continuous shrink in detailing of micro-electronics and MEMS. As well as the more frequently presented standard subjects of dynamics, motion control, electronics and electromechanics, this.